Effectiveness of sound-working memory therapy for autism spectrum disorder (ASD) children using malay emotion regulation checklist (ERC-M) - Jamal, Fatin Nabilah; Dzulkarnain, Ahmad Aidil Arafat; Shahrudin, Fatin Amira; Jusoh, Masnira; Ahmad Basri, Nadzirah; Musa, Ramli; Sidek, Shahrul Naim; Md Yusof, Hazlina; Abd Hamid, Siti Rafiah (2023)
Objective: To investigate the effectiveness of sound and working therapy intervention among ASD children using the Malay Emotional Regulation Checklist (ERC-M). Participants and Methods: Thirty five ASD children aged between 6 and 14 years participated. All participants were assigned to two control groups and three experimental groups. The control groups were subdivided into the group with sound therapy only (white noise) and without sound therapy. The experimental groups were subdivided into group trained with different sounds therapy as follows: waterfall, white noise, and Quranic recitation and was conducted concurrently with the working memory training (WMT) task. Parents were required to fill in the ERC-M for pre and post sound-working memory therapy intervention. Results: Repeated Measure (RM) ANOVA analysis identified a significantly higher post-therapy ERC-M scores with large effect size for Liability/ Negativity (L/N) domain in participant from Quranic Recitation with WMT group and large effect size for Emotion Regulation (ER) domain in participant from white noise group. Based on both statistical analysis and effect size, the highest gain score (post-pre score differences) was observed from Quranic Recitation group, followed by white noise, waterfall, sound therapy only (white noise) group and control group without sound therapy. The results suggested that the highest gain in both ER and L/N obtained from Quranic Recitation might be because of the spiritual effect that improves the emotion regulation. The white noise has the second largest gain of improvement possibly due to the bandwidth spectrum of the sounds able to be trained and altered the emotional parts of the brain in ASD. Conclusions: The current study suggests that the combination of both sound and working memory therapy has the potential to regulate emotions among ASD children, as revealed through ERC-M. This study identifies Quranic recitations and white noise as possible sound types to be used in sound-working memory therapy in future studies.